2011
DOI: 10.1057/ajp.2010.40
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Entitlement in Couple Relationships: An Attachment Theory Perspective

Abstract: Our sense of entitlement is activated and influences our interactions and attitudes in a wide range of contexts, but it seems to have special relevance to couple relationships, as these intimate relationships serve as a unique meeting point between needs, wishes, and expectations. Emphasis is placed on the connection between one's sense of entitlement in a romantic relationship and early experiences of entitlement in the context of relationships with primary caregivers. An understanding of the development of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 26 publications
2
35
0
1
Order By: Relevance
“…Tolmacz and Mikulincer (2011) found that sense of entitlement was related to adult attachment insecurity in the form of attachment anxiety (indicating a preoccupied style) and avoidance (indicating a fearful and/or dismissive style). Aside from these findings, research on links between entitlement and adult attachment is limited, with much of the research on entitlement and adult attachment focusing instead on relational entitlement -the belief that one deserves more than their partner in romantic relationships -and childhood attachment to parents (e.g., Tolmacz, 2011;Tolmacz and Mikulincer, 2011;Rothman and Steil, 2012;Shadach et al, 2018). There are many reasons to expect that an exaggerated sense of entitlement may interact with adult attachment style and influence narcissistic pathology.…”
Section: Pathological Narcissism and Adult Attachment Stylesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tolmacz and Mikulincer (2011) found that sense of entitlement was related to adult attachment insecurity in the form of attachment anxiety (indicating a preoccupied style) and avoidance (indicating a fearful and/or dismissive style). Aside from these findings, research on links between entitlement and adult attachment is limited, with much of the research on entitlement and adult attachment focusing instead on relational entitlement -the belief that one deserves more than their partner in romantic relationships -and childhood attachment to parents (e.g., Tolmacz, 2011;Tolmacz and Mikulincer, 2011;Rothman and Steil, 2012;Shadach et al, 2018). There are many reasons to expect that an exaggerated sense of entitlement may interact with adult attachment style and influence narcissistic pathology.…”
Section: Pathological Narcissism and Adult Attachment Stylesmentioning
confidence: 99%
“…These caregiver conditions are akin to those that are thought to generate attachment security which may translate to greater security in adulthood. Conversely, an exaggerated sense of entitlement (often seen in narcissistic presentations) has been theorized to emerge from parental behavior that is insensitive to needs, but occasionally over indulgent (Meyer, 1991;Tolmacz, 2011), and early trauma (Moses and Moses-Hrushovski, 1990). Whilst quality of early attachments to caregiver may be relevant to the development of entitlement, research addressing current attachmentparticularly Bartholomew and Horowitz's four category modeland entitlement as part of a narcissistic presentation is scarce.…”
Section: Pathological Narcissism and Adult Attachment Stylesmentioning
confidence: 99%
“…SRE has generally been conceived in pathological terms, for example, as a criterion for psychopathy (Hare, 1999), or narcissistic personality disorder (American Psychiatric Association, 2000). Some researchers have, however, suggested a different perspective and framed SRE in the context of attachment theory (Tolmacz, 2011; Wolfe & Bailey, 2003). According to this perspective, infants learn about their entitlement from the unique response of primary caregivers to their demands.…”
Section: Introductionmentioning
confidence: 99%
“…40 -63 ;Tolmacz, 2011 ). As might be expected both his wife and their therapist agreed to " honor " (or colluded with) his insistent desire.…”
Section: Frankmentioning
confidence: 86%